The transport of polyphenols from Camellia fascicularis in Caco-2 cells based on UPLC-ESI-MS/MS - Shengjiang Duan; Hao Zheng; Junrong Tang; Huan Kan; Changwei Cao; Zhijiao Shi; Yun Liu (Food Chemistry: X)
Camellia fascicularis, as a food and medicinal plant, is rich in polyphenols. Herein, digestion samples (DS) of C. fascicularis polyphenols (CFPs) were metabolically analyzed based on their bidirectional translocation in Caco-2 cells using ultraperformance liquid chromatography-electrospray ionization-tandem mass spectrometry. The results indicated that after DS transported via Caco-2 cell monolayer models nine polyphenol compounds in transit solution (TSB) from apical (AP) to basolateral (BL) side were upregulated, whereas seven in the transit solution (TSA) from BL to AP side were upregulated. In addition, 53 significantly different polyphenol compounds dominated by flavonoids were identified in the TSA vs. TSB groups, with a dominantly moderate degree of uptake. Among them, 40 polyphenol compounds were upregulated including eupatorin, 5,7,4′-trihydroxy-3,6,3′,5′-tetramethoxyflavone, and jaceosidin-7-O-glucoside, which might exhibit active transport, whereas the remaining 13 were downregulated and might exhibit passive diffusive transport. This study offers a rationale that further explored the bioactive mechanisms of CFPs.